Effects of Plant Growth Promoting Bacteria on Growth and Essential Oil Production of Peppermint - Abdul Wase Tajzadah; Shafiqullah Rahmani; Ghulam Maruf Faqiri (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Peppermint is abundant with organic compounds having therapeutic, coloring, preservative, and other uses for humans. Moreover, peppermint is used in food and perfume industry and as medicine in every corner over the world. Considering the economic and medicinal value of peppermint, there is a significant gap between supply and demand. Therefore, an analysis of the impact of bacteria that promote plant development was carried out on peppermints (Pseudomonas putida and Curtobacterium sp. strain LUW) essential oil production. Under the study, the plant growth parameters, essential oil, chlorophyll and carotenoids, and free proline of leaves were measured. The outcomes demonstrated that the use of both Pseudomonas and Curtobacterium (Plant Growth Promoting Bacteria) in the soil significantly increased root diameter, leaf area, leaf number, plant height, quantity of stems, root length, root volume, dry weight of leaf, and peppermint plants' relative water content by 34.29, 23.34, 36.57, 21.08, 87.5, 12.28, 20.37, 42.62, and 6.46 compared to the control conditions respectively. Furthermore, the application of bacteria in the soil that promotes plant growth raised the total quantity of essential oil, proline, and chlorophyll concentration in the leaf by 50.90, 20.90, and 33.35%, respectively, compared to the control conditions. Moreover, essential oil and proline content increased with Curtobacterium sp. strain application compared to Pseudomonas putida.